2002
DOI: 10.1063/1.1488147
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of calibration procedures for accurate determination of thermal parameters of liquids and their temperature dependence using the photopyroelectric method

Abstract: Articles you may be interested inHigh accuracy, self-calibrating photopyroelectric device for the absolute determination of thermal conductivity and thermal effusivity of liquids Rev. Sci. Instrum. 80, 054904 (2009); 10.1063/1.3131625 On the accurate determination of thermal diffusivity of liquids by using the photopyroelectric thickness scanning method Rev. Sci. Instrum. 78, 024902 (2007);We present a systematic theoretical and experimental investigation on the accuracy of thermal diffusivity ␣ and thermal ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 19 publications
(28 reference statements)
2
29
0
Order By: Relevance
“…The eq. (7) is similar in form to the one reported by Delenclos et al but with different constant C 10 . The constant C is trivial in obtaining the value of thermal diffusivity and that is the reason why we do not consider the sample reflectivity, which is sample dependent and remains constant at single laser wavelength, in our model.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The eq. (7) is similar in form to the one reported by Delenclos et al but with different constant C 10 . The constant C is trivial in obtaining the value of thermal diffusivity and that is the reason why we do not consider the sample reflectivity, which is sample dependent and remains constant at single laser wavelength, in our model.…”
Section: Methodssupporting
confidence: 75%
“…Minamide et al 8 applied the theory of thermal wave propagation suggested by Opsal and Rosencwaig 9 , in which a thermally inhomogeneous material was modeled with a system of N plane homogenous layers, to a 3-layer structure consists of graphite, air-gap and polyvinylidene diflouride (PVDF) film. In the contact method by Delenclos et al 10 , a difficult task is involved in solving 10×10 matrix by Cramer' s rule to obtain the solution for a heat transfer equation in order to reach the final expression for the average PPE voltage. In the normalization procedure, they normalized the liquid sample signal with respect to sensor signal alone, and also to other liquid sample signal.…”
Section: Introductionmentioning
confidence: 99%
“…Among other mixtures, water-alcohol solutions are of special interest, mostly in chemical, food, and environmental applications. Up to now, a variety of techniques have been employed for the measurement of the thermal diffusivity of alcohols and water-alcohol mixtures [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Photon correlation spectroscopy has been used in measurements of pure alcohols and their binary mixtures [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The thermal diffusion length depends on the thermal diffusivity a and chopping frequency f as m = (a/pf) 1/2 . The symbols "m", "p" and "w" refer to material (sample), pyroelectric sensor and window, respectively [10,12,13].…”
Section: Theorymentioning
confidence: 99%